Mechanical and physical stability of polyhydroxyalkanoate (PHA)-based wood plastic composites (WPCs) under natural weathering. (February 2019) - Chan, Clement Matthew; Pratt, Steven; Halley, Peter; Richardson, Desmond; Werker, Alan; Laycock, Bronwyn; Vandi, Luigi-Jules
Abstract: This study investigated the effects of natural weathering on the physical and mechanical properties of biodegradable composites based on poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) and wood flour (WF). Composite samples with three different wood contents (0, 20 and 50 wt%), as well as polylactic acid (PLA) and polyethylene (PE) composites containing 50 wt% of WF, were placed on an outdoor inclined rack for 12 months. Neat PHBV and the 20% WF samples showed minimal mould growth and little loss in mechanical properties over the 12-month period. By contrast, the tensile strength of the composites (of all polymer types) made with 50% WF dropped gradually. This decrease was interpreted to be due to the evolution of surface/bulk defects brought about by the degradation of wood particles from moisture-induced fungal (mould) attack. Overall, the wood content and the accessibility of wood particles inside the matrix control the stability of the composites under natural weathering. Highlights: UV exposure resulted in surface whitening of PHA and their composites. Neat PHA was physically and mechanically stable upon natural weathering. PHA composites behaved similarly to PLA and PE composites upon natural weathering. Wood is the species responsible for mechanical deterioration due to mould growth. Partial sealing of wood flour by hydrophobic PHA provided protection from mould.